№664 Преобразуйте произведение в многочлен а)3ab (a^2-2ab+b^2); b)-x^2y(x^2y^2-x^2-y^2); c)2,5a^2b(4a^2-2ab+0,2b^2); d)(-2ax^2+3ax^2-a^2)(-a^2x^2); e)(6,3x^3y-3y^2-0,7x)*10x^2y^2; f)(-1,4p^2q^6(5p^3q-1,5pq^2-2q^3).
№664 Преобразуйте произведение в многочлен
а)3ab (a^2-2ab+b^2);
b)-x^2y(x^2y^2-x^2-y^2);
c)2,5a^2b(4a^2-2ab+0,2b^2);
d)(-2ax^2+3ax^2-a^2)(-a^2x^2);
e)(6,3x^3y-3y^2-0,7x)*10x^2y^2;
f)(-1,4p^2q^6(5p^3q-1,5pq^2-2q^3).
Ответ(ы) на вопрос:
а)3ab (a^2-2ab+b^2)=3a³b-6a²b²+3ab³
b)-x^2y(x^2y^2-x^2-y^2)=-x^4y³+x^4y+x²y³
c)2,5a^2b(4a^2-2ab+0,2b^2)=10a^4b-5a³b²+0,5a²b³
d)(-2ax^2+3ax^2-a^2)(-a^2x^2)=2a³x^4-3a³x^4+a^4x²
e)(6,3x^3y-3y^2-0,7x)*10x^2y^2=63x^5y³-30x²y^4-7x³y²
f)(-1,4p^2q^6(5p^3q-1,5pq^2-2q^3)=-7p^5q^7+2,1p³q^8+2,8p²q^9
а)
[latex]=3a^3b-6a^2b^2+3ab^3[/latex]
b)
[latex]=-x^4y^3+x^4y+x^2y^3[/latex]
c)
[latex]= 10a^4b-5a^3b^2+0.5a^2b^3[/latex]
d)
[latex]=2a^3x^4-3a^3x^4+a^4x^2[/latex]
e)
[latex]=63x^5y^3-30x^2y^4-7x^3y^2[/latex]
f)
[latex]= -7p^5q^7+2.1p^3q^8+2.8p^2q^9[/latex]
Не нашли ответ?
Похожие вопросы